Spontaneous chiral symmetry breaking in holographic soft wall models - Ballon-Bayona, Alfonso; Mamani, Luis A. H.; Rodrigues, Diego M. [UNESP] (American Physical Society (APS), 2021)
We investigate nonlinear extensions of the holographic soft wall model proposed by Karch et al. [Phys. Rev. D 74, 015005 (2006)PRVDAQ1550-799810.1103/PhysRevD.74.015005] including nonminimal couplings in the five-dimensional action. The nonminimal couplings bring a new parameter a0 which controls the transition between spontaneous and explicit symmetry breaking near the limit of massless quarks (the chiral limit). In the physical region (positive quark mass), we show that above a critical value of the parameter a0 the chiral condensate ⟨q¯q